2006
DOI: 10.1111/j.1442-2042.2006.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of 36 male patients with primary urethral carcinoma: A single center experience

Abstract: Aim : Retrospective analysis of male urethral carcinoma to assess the best therapeutic approach to the management of this tumor. Methods : A review of 36 cases of male urethral carcinoma diagnosed and treated at our center was performed. Clinical features, treatment modality and outcomes were analysed. Results : The overall median survival time was 55.16 months. The 5-year overall and disease-free survival rate for the cohort was 49% and 23%, respectively. The 5-year survival is 67% for low-stage versus 33% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…In total, 14 out of 17 patients suffered a recurrence and the 5-year survival rate for proximal urethral tumours was 36%, compared with 72% for distal urethral tumours. 31 Dalbagni et al 21 also reported similar 5-year survival rates of 26% and 69%, for proximal and distal urethral cancers, respectively. Christopher et al 37 presented an innovative approach to a patient with a T4 bulbo-membranous tumour whom was reluctant to undergo emasculative surgery.…”
Section: Surgery For Proximal Primary Urethral Carcinomamentioning
confidence: 83%
See 1 more Smart Citation
“…In total, 14 out of 17 patients suffered a recurrence and the 5-year survival rate for proximal urethral tumours was 36%, compared with 72% for distal urethral tumours. 31 Dalbagni et al 21 also reported similar 5-year survival rates of 26% and 69%, for proximal and distal urethral cancers, respectively. Christopher et al 37 presented an innovative approach to a patient with a T4 bulbo-membranous tumour whom was reluctant to undergo emasculative surgery.…”
Section: Surgery For Proximal Primary Urethral Carcinomamentioning
confidence: 83%
“…Dinney et al 2 achieved good control in tumours arising from the navicular fossa, with either distal urethrectomy or partial penectomy, with no cases of recurrence 2 ; however, 4 out of 11 patients with disease arising from the penile urethra died of recurrent disease. Thyavihally et al 31 report having 58% recurrence free and 72% 5-year survival for 12 patients with distal urethral cancer, treated with partial penectomy (n = 9) and adjuvant radiotherapy, and in two cases adjuvent chemotherapy was also used. Surgery for distal urethral lesions continues to evolve: Current practice aims to preserve penile length, in order to improve both functional and psychological outcomes following surgery.…”
Section: Surgery For Distal Primary Urethral Carcinomamentioning
confidence: 99%
“…In addition, some studies show that the location of the lesion also interferes with the prognosis, being the involvement of the proximal urethra present in more aggressive cases [17]. There are not many studies comparing the different histological types of urethral cancer, and those which discuss this subject are based only on case reports; this happens due to the rarity of this neoplasia.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of 36 cases, with 36% distal tumors and 64% proximal tumors, being 72% squamous cell carcinoma, 25% transitional cell carcinoma and 3% adenocarcinoma, patients underwent neoadjuvant pelvic radiotherapy and chemotherapy with five-fluorouracil and cisplastin, with extensive surgical resection of tumors, ranging from partial penectomy (distal tumors) to radical cystectomy, radical penectomy and ileal conduit (invasive proximal tumors) [17].…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of patients (usually men) with tumors of the anterior urethra have better outcomes, with reported disease-free survival of 52% after a mean follow-up of 50 months [6]. Distal urethral tumors tend to be of low stage, and cure rates of 70% to 90% after local surgical excision and radiation therapy have been reported in some series [7]. Most cases (66%) of PCU, however, involve the proximal urethra, and they tend to be more advanced and are associated with a 5-year disease-free survival rate of only 20% to 30% with surgery alone [7].…”
Section: Introductionmentioning
confidence: 99%